Association between household size and risk of incident dementia in the UK Biobank study - Cong, Chao-Hua; Li, Pan-Long; Qiao, Yuan; Li, Yu-Na; Yang, Jun-Ting; Zhao, Lei; Zhu, Xi-Rui; Tian, Shan; Cao, Shan-Shan; Liu, Jian-Ren; Su, Jing-Jing (Scientific reports, 2024)
Currently, the relationship between household size and incident dementia, along with the underlying neurobiological mechanisms, remains unclear. This prospective cohort study was based on UK Biobank participants aged ≥ 50 years without a history of dementia. The linear and non-linear longitudinal association was assessed using Cox proportional hazards regression and restricted cubic spline models. Additionally, the potential mechanisms driven by brain structures were investigated by linear regression models. We included 275,629 participants (mean age at baseline 60.45 years [SD 5.39]). Over a mean follow-up of 9.5 years, 6031 individuals developed all-cause dementia. Multivariable analyses revealed that smaller household size was associated with an increased risk of all-cause dementia (HR, 1.06; 95% CI 1.02–1.09), vascular dementia (HR, 1.08; 95% CI 1.01–1.15), and non-Alzheimer’s disease non-vascular dementia (HR, 1.09; 95% CI 1.03–1.14). No significant association was observed for Alzheimer’s disease. Restricted cubic splines demonstrated a reversed J-shaped relationship between household size and all-cause and cause-specific dementia. Additionally, substantial associations existed between household size and brain structures. Our findings suggest that small household size is a risk factor for dementia. Additionally, brain structural differences related to household size support these associations. Household size may thus be a potential modifiable risk factor for dementia.